Effect of flue gas composition on deposit induced high temperature corrosion under laboratory conditions mimicking biomass firing. Part II: Exposures in SO2 containing atmospheres. Issue 5 (6th December 2016) - Okoro, S. C.; Kiamehr, S.; Montgomery, M.; Frandsen, F. J.; Pantleon, K.
Abstract : In biomass fired power plants, the fast corrosion of superheaters is facilitated by the presence of corrosive flue gas species, for example, SO2, which are released during combustion. To understand the role of the gas species on the corrosion process, comparative laboratory exposures of deposit (KCl)‐coated and deposit‐free austenitic stainless steel (TP 347H FG) samples to gas mixtures containing SO2 was carried out, under conditions relevant to biomass‐firing. Exposures were conducted isothermally at 560 °C for 72 h, in oxidizing‐sulphidizing, and oxidizing‐sulphidizing‐chlorinating gas mixtures containing 60 ppmv SO2 . Scanning electron microscopy (SEM), energy dispersive X‐ray spectroscopy (EDS) and X‐ray diffraction (XRD) techniques were complimentarily applied to characterize the resulting corrosion products. A partially molten K2 SO4 ‐layer formed on KCl coated specimens, and corrosion resulted in localized broad pits containing sulphides and oxides. The severe pitting attack was decreased by the presence of HCl in the gas mixture. Abstract : The effect of SO2 in the flue gas is investigated to evaluate its role on high temperature corrosion of superheaters under conditions mimicking biomass firing. Results show that when a deposit is absent, SO2 minimizes corrosion attack. Deposit (KCl) particles are sulphated due to the presence of SO2 in the flue gas and the resulting corrosion attack on deposit‐coated samples involves severe local pitting, which is minimized when HCl is added to the flue gas.